PENERAPAN METODE STRAIGHT SELECTION PADA SISTEM PARKIR UNIVERSITAS BINA NUSANTARA - Maharani, Mega; Merlina, Nita (LPPM Universitas Nusa Mandiri, 2014)
The parking information System is designed to develop the current system that has been employed at BINA NUSANTARA University. Currently, the parking system is limited only recording the police number and they are still manually looking for the available parking area. The system implements a straight selection sorting data method, also known as the smallest number search method to determine the available parking location. The parking area will be automatically printed at a parking ticket, thus the driver could find it easily. This method also provides accurate data for building management about the available parking area and all data needed about the vehicles that parked at that area. This research is software based on web program using internet access.